Nautical knots illustrated - Snyder, Paul; Snyder, Arthur (McGraw Hill, 2002)
With nearly 300 superb photographs illustrating the "ins and outs" of the 20 most useful nautical knots and splices, this reissue of the critically acclaimed Nautical Knots Illustrated will transform any beginner into a boater who knows the ropes. Each knot or splice is presented on two facing pages, and an illustrated glossary and quick-glance overview of common linehandling commands are also included.